2015
DOI: 10.1177/155892501501000111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Towels Produced from Twisted and Twistless Cotton Pile Yarns in Terms of Absorptive Capacity and Flexural Rigidity

Abstract: The study compares cotton towels produced from twisted and twistless cotton pile yarn. The towels were manufactured with different weft density, different weft yarn counts, and different pile heights. The water absorptive capacity, absorbency time and flexural rigidity properties of twisted pile towels were compared with those of twistless pile towels. The test results were evaluated using statistical analysis. Effects of twisted and twistless pile yarn, pile height, weft density, and weft yarn count on absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…between yarn count and twist multiplier. Results of the second-order interaction effect among the three studied factors (cotton materials, yarn count and twist multiplier) on towel comfort properties are presented in Table (9). It is revealed that the interaction effect was no significant for all towel comfort properties indicating that each one of the three studied factors reflect similar behavior under the other two variables.…”
Section: Table (8): the Average Values Of Comfort Properties For Towe...mentioning
confidence: 97%
“…between yarn count and twist multiplier. Results of the second-order interaction effect among the three studied factors (cotton materials, yarn count and twist multiplier) on towel comfort properties are presented in Table (9). It is revealed that the interaction effect was no significant for all towel comfort properties indicating that each one of the three studied factors reflect similar behavior under the other two variables.…”
Section: Table (8): the Average Values Of Comfort Properties For Towe...mentioning
confidence: 97%
“…Terry towel is a texture with circles on a superficial level possibly a couple of sides of the texture that can retain immense measure of water contrasted with regular structure. (13). Terry towel texture is one of the principle customer merchandise being utilized by individuals around the world.…”
Section: Introductionmentioning
confidence: 99%